Futuros professores e a organização o ensino: o clube de matemática como espaço de aprendizagem da docência - Fraga, Laura Pippi (2013)
This dissertation is inserted into the Research Line Formação, Saberes e Desenvolvimento Profissional and has its focus on a space of discussion upon Pedagogy and Mathematics future teachers education from Universidade Federal de Santa Maria, that teach Mathematics in the early years of elementary school. The main purpose is to investigate the learning of teaching activity from future teachers in a process of Mathematics teaching organization for the first grades of elementary school. For that, the study focused on the organization of activities at Mathematics Club CluMat, where proposals for teaching Mathematics in the early years are studied, planned, developed and evaluated, having as theoretic-methodological framework the Teaching Orientating Activity AOE (MOURA, 1996, 2001). The data analysis was based on the historic-cultural perspective, in special Vigotsky (2002) and Leontiev (1978), that lead us to comprehend that human being learns in interaction with other individuals and that through activities, they take the culture in which is inserted. Thus, we analyzed four steps that compose the teaching organization at CluMat, they are: Mathematics subject study; the planning; the development; and the evaluation. To collect the data, we followed the participation, inside this space, of five future teachers four from Pedagogy and one from Mathematics Course through the observation of meetings and also a questionnaire. To present and analyze these, we used the idea of episodes, proposed by Moura (2004). We composed four guiding topics: 1 - Studying Mathematics: Statistics in the early years; 2 - Planning together: the case of AOE on Statistics; 3 - Developing the AOE: Statistics at Mathematic Club; 4 Evaluating the AOE: rethinking on the practice at Mathematic Club. From the analysis, we concluded that the different situations lived at CluMat brought new learning to the future teachers. By acting together, students from Pedagogy and from Mathematics Courses, both with knowledge of different areas, are motivated by the same purposes and, despite the differences, they complement each other, aiming to supply the need of teaching organization. In this context, we verified that, organizing the teaching by sharing the actions, the future teachers learned, in the teaching activity, reevaluating the activity and improving their teacher practice.